Weight Change and Predictors of Weight Change Among Patients Initiated on Darunavir/Cobicistat/Emtricitabine/Tenofovir Alafenamide or Bictegravir/Emtricitabine/Tenofovir Alafenamide: A Real-World Retrospective Study - Bruno Emond; Carmine Rossi; Aurélie Côté-Sergent; Keith Dunn; Patrick Lefebvre; Marie-Hélène Lafeuille; Prina Donga (Journal of Health Economics and Outcomes Research)
**Background:** Recent evidence suggests that integrase strand transfer inhibitors are associated with greater weight gain than protease inhibitors in patients with human immunodeficiency virus (HIV-1).